A Critical Analysis of al-Bayhaqi Hadith on Tolerance in the Preservation of Houses of Worship in Dalāil al-Nubuwwah - Mukoyah, Mukoyah; Raharusun, Agus Suyadi; Nur, Saifudin; Ahmed, Ismail Ibrahim el-Sayed (Diroyah : Jurnal Studi Ilmu Hadis, 2024)
Tolerance is fundamental in Islam, encompassing compassion towards others, regardless of their background. Based on the Qur'an and Hadith, tolerance is an essential value in Islam that is crucial for maintaining national integrity and creating stability to achieve a united and prosperous society. This study aims to assess the quality of the Hadith narrated by Al-Bayhaqi regarding tolerance in the maintenance of places of worship and to understand the views of Hadith scholars on tolerance in this context. This study employed a qualitative approach using qualitative data-collection techniques. Content analysis and the Syarah method were used for analysis. Imam al-Baihaqi's book “Dala'il an-Nubuwwah” presents evidence of the truth and prophethood of Prophet Muhammad (PBUH). The findings show that the Hadith under study is classified as “Hasan Lighairihi” because it is a mursal Hadith strengthened by other Hadiths. Scholars have varying views on tolerance in the maintenance of non-Muslim places of worship, with some hadiths regulating protection and prohibiting actions that could threaten them. In a contemporary context, Indonesia's multireligious society reflects religious diversity, with laws protecting religious freedom stipulated in Article 29 of the 1945 Constitution of the Republic of Indonesia